(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This study examines the Pragmatic meanings of names in Hausa. One hundred and ten data gathered from Hausa names have been purposely selected for Pragmatic analysis because of their assertive, penetrating, and insightful messages. The connotational meaning of the selected names was analysed using the pragmatic and linguistic tools of context. The study examines the pragmatic inferences of the names by exploring the reasons and circumstances of the selected names. The names were purposively selected through primary and secondary methods. The data were grouped according to different circumstances surrounding the names. The findings from this study shows that Hausa names do not only identify a person but also communicate so much about the circumstances surrounding the person’s birth. Another significant reason is the fact that Hausa people have now recognized the importance of preserving Hausa language. The study concludes that names perform several practs like informing, assuring, pronouncing, or expressing gratitude which are reflective of the emotional link or expectations of the giver of the personal name.